Understanding China : navigating the road ahead - Keane, Michael (Societa Editrice Il Mulino, 2009)
This paper proposes an alternative way of understanding China’s emergence, drawing on the idea of the creative industries. It looks at China’s embrace of the idea of cultural and creative industries and argues that this paradigm demonstrates that structures of domination (i.e. the commanding heights of political economy exemplified in political economy of the media) are being replaced by geographical development initiatives, mostly led by local governments and councils. In this decentralisation of power we find the seedlings of a more open and democratic society.